2014
DOI: 10.1007/s12663-014-0658-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Different Methods of Arch Bar Application: A Comparative Prospective Study

Abstract: Purpose To comparatively evaluate the efficacy of a pencil type wire twister and the normal wire twister in terms of various parameters during arch bars application. Method The study involved residents of the department enrolled in MDS course. Two study groups of 60 patients each were made by randomly selecting the patients from the outpatient department of Oral and Maxillofacial surgery who required arch bar application. Group A included the patients who underwent upper and lower arch bar application with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…An orthodontist's skill, experience and attention are important because of the extensive use of cutting instruments and metallic ligatures during fixed orthodontics. Specific preventive strategies to reduce the risk of infection due to the puncture of a glove-covered hand include reducing the use of sharp objects by favouring elastomeric ligatures (when clinically possible), selfligating brackets, pencil-type twisters (that reduce glove perforation and wire stick injuries), and surgical alternatives to rapid intermaxillary fixation (inter-maxillary fixation screws etc) (49). Damage to the intra-oral tissues of patients (mucosal trauma) must be prevented by using functioning instruments: any sign of "wear or work fatigue" and any damage to the cutting tips of orthodontic instruments must be promptly identified, and the tip or instrument immediately replaced (10).…”
Section: Percutaneous Injuries and Glovesmentioning
confidence: 99%
“…An orthodontist's skill, experience and attention are important because of the extensive use of cutting instruments and metallic ligatures during fixed orthodontics. Specific preventive strategies to reduce the risk of infection due to the puncture of a glove-covered hand include reducing the use of sharp objects by favouring elastomeric ligatures (when clinically possible), selfligating brackets, pencil-type twisters (that reduce glove perforation and wire stick injuries), and surgical alternatives to rapid intermaxillary fixation (inter-maxillary fixation screws etc) (49). Damage to the intra-oral tissues of patients (mucosal trauma) must be prevented by using functioning instruments: any sign of "wear or work fatigue" and any damage to the cutting tips of orthodontic instruments must be promptly identified, and the tip or instrument immediately replaced (10).…”
Section: Percutaneous Injuries and Glovesmentioning
confidence: 99%
“…Similar injuries have been reported in the literature as a common problem. [14] There was no frictional abrasion over the finger recorded in placing the arch bar in the group B.…”
Section: Discussionmentioning
confidence: 78%
“…Chhabra et al 4 compared the pencil-type wire twister with the traditionally used wire twister and found that the pencil-type twister had lower counts of mean glove perforations, as well as wire injuries to fingers; mean time taken to complete the procedure; and mean wire breakage during the procedure.…”
mentioning
confidence: 99%